Medication overuse headache: a pragmatic 5-year, real-world study - Krymchantowski, Abouch; Jevoux, Carla; Krymchantowski, Ana Gabriela; Dominguez Moreno, Rogelio; Silva-Néto, Raimundo Pereira (Headache Medicine, 2025)
Background Medication overuse headache (MOH) impacts 1-7% worldwide. Effective treatment involves the abrupt discontinuation of the overused medication, the implementation of transition therapy during the initial period, and the simultaneous commencement of preventive treatment. Objective To describe a 5-year follow-up of patients with chronic migraine and MOH, focusing on the effectiveness of withdrawal treatment, use of traditional preventive medication, and requirement of anti-CGRP monoclonal antibodies. Method A single-center, prospective, and descriptive study was conducted. Convenience sampling of consecutive patients diagnosed with chronic migraine and MOH was the inclusion criterion. Demographics and clinical data at baseline, at 12 months, and during a follow-up period of 5 years, were collected in clinical records. The statistical analyses were performed with the Statistical Package for Social Sciences (SPSS®) version 18.2.2. Results We were able to follow one hundred and forty patients (116 W, 26 M), ages 18-78 years (mean 42.1±14.3) for 5 years. The diagnosis was carried out 24.9±14.7 years after the onset of the headache, and 6.3±7.6 years, was the time with headache ≥15 days per month. On baseline, the average number of headache days per month (HDM) was 25.2±5.9. There was a meaningful reduction in HDM. At 1 year and 5 years, a ≥ 75% reduction in HDM was observed, respectively, in 51.4% and 70.4% of the sample. Conclusions After five years, patients with chronic migraine and MOH who withdrew from excessive medication, used preventive pharmacological agents, and optionally added anti-CGRP monoclonal antibody showed a significant decrease in HDM frequency.